Discovery Learning dalam Pembelajaran PPKn - Ustanti, Dwi (Universitas Sebelas Maret, 2020)
Education is a learning process so that active students are skilled, intelligent and have noble character. The purpose of this study (1) The students are active in learning, (2) The students are able to understand of PPKn (2) The students learning outcomes are increase. The results of this stusy is the students are active, understand of PPKn and the learning outcomes are increase.